Uji Patogenesitas Oospora Peronospora manshurica Asal Kedelai Impor pada Tiga Kultivar Kedelai - Ani Ardiana Susanti; Marlina Marlina; Husda Marwan; Mapegau Mapegau (Universitas Batanghari, 2021)
Downy mildew in soybean plants is caused by the fungus Peronosporamanshurica. This fungus is an obligate parasite and its existence in Indonesia is still limited. This study aims to determine the pathogenicity of the fungus P. manshurica carried on imported seeds of soybeans from Malaysia. The Oospora from imported soybean seeds from the Class I Agricultural Quarantine Center was tested for its pathogenicity on soybean cultivars Anjasmoro, Grobogan, and Wilis in the greenhouses of the Jambi Class I Agricultural Quarantine Center. This test used a completely randomized design (CRD), using 4 treatments; 3 superior soybean cultivars (Anjasmoro, Grobogan, and Wilis),and 1 imported soybean cultivar. Each treatment was repeated 6 times so that there were 24 experimental units and each experimental unit consisted of 5 plants so that the total number was 120 plants. The results showed that the pathogenicity of the Oospore ofP.manshurica from imported soybean seeds still caused downy disease in the three soybean cultivars tested. There was no difference in the incubation period of downy mildew caused by the Oospora ofP.manshurica on Anjasmoro, Grobogan, and Wilis cultivars, which were 5.5, 8.0, and 7.0 days after inoculation, respectively. The highest disease severity was found in the Anjasmoro cultivar (8.91%) and the lowest was in the Wilis cultivar (2.66%), but it was not different from the disease severity in the Grobagan cultivar (4.28%).